Un nuevo método de estudio de la ciclicidad en el crecimiento de las escamas ganoideas, aplicado a Fontllonga3 (PaleocenoInferior,Lleida) - Iglesias Martin, Isabel; Soler Gijon, Rodrigo (Coloquios de Paleontología, 1999)
This paper deals with the morphology and histology of ganoid scales (lepidosteoid type) from the Early Palaeocene of Fontílonga 3 (Lleida, Spain). in order to establish its growth pauerns. A new technique of analysis of the growth of the ganoid scales is descnbed. Allometric growth of Ihese ganoid scales is described in detail. The interruptions of the ganoine layers preclude the use of rings counting methods. The new nielbod consists on rhe measurement of the length of the steps of the ganoine laycrs on the ganoineisopedine interface in trausverse section. Data are represented in bivariate plots showing number of ganoine layers (from te embryonic central area outwards) against length (in ~1m) of each ganoine step overlapping the isopedine. These chasIs enable lo distinguish the growth cycles of the ganoine, and then to compare the ganoine growlh patrern with that of the isopedine. Growth rythms are closely related ro physiological varintions, which are synchrouized to environmental changes (mainly ctimatic and geographic): therefore te síudy of growtli patterns allows infersing palaeoenvironnieníal conditions. Key wonls: Sk'eletochronology, Cycliciry, Actinopterygians, Ganoid scales, Ca¡mine, Isopedine, Lower Palaeocene, Pyrenees.